Discover the answers you need at Westonci.ca, a dynamic Q&A platform where knowledge is shared freely by a community of experts. Experience the ease of finding reliable answers to your questions from a vast community of knowledgeable experts. Connect with a community of professionals ready to provide precise solutions to your questions quickly and accurately.

3.) Solve:
5x + 3- 3x = 2(x + 3) - 5


Sagot :

Answer:

0 = -2

Step-by-step explanation:

Answer:

no answer.

Step-by-step explanation:

5x + 3 - 3x = 2(x + 3) - 5             Simplify the left.

2x + 3 = 2(x + 3) - 5                    Remove the brackets

2x + 3 = 2x + 6 - 5                      Simply the right

2x + 3 = 2x + 1                            

It doesn't matter what you do, this is going to give you an impossible answer. The 2x's will cancel out and you will get 3 = 1 which is impossible.